Maqāṣid al-Sharī‘a and FKUB: Tracking Potentiality for Religious Harmony in Indonesia - Romdhoni, Rizki (Sekretariat Badan Moderasi Beragama dan Pengembangan Sumber Daya Manusia (BMBPSDM) Kementerian Agama RI, 2024)
Abstract The idea of Maqāṣid al-Sharī’a (the objectives of Islamic law) has been widely discussed within the Muslim world. This is because the normative values of Maqāsid are universal. So that, it is often used as a sharī’a-based approach to analyze ongoing religious phenomena. In the FKUB (Forum Kerukunan Umat Beragama/forum for religious harmony) context, inter-religious harmony problems that occur in the midst of society caused by FKUB policies have not been minimized. This gives the impression that the public benefit (maṣlaḥa), as the basic principle of maqāṣid sharī'a, experiences obstacles in creating harmony for Indonesian society, the majority of which are Muslims. In order to analyze it, this paper uses content analysis as its method. I will analyze the concepts of maqāṣid and the rights of religious freedom through two prominent Muslim thinkers, Jaser Auda and Yudian Wahyudi. I argue that FKUB's policies need to be revised by considering the concept of maslaḥa and the criticisms submitted to them.